Escalating low‐dose Δ9‐tetrahydrocannabinol exposure during adolescence induces differential behavioral and neurochemical effects in male and female adult rats. (9th November 2019) - Poulia, Nafsika; Delis, Foteini; Brakatselos, Charalampos; Lekkas, Panagiotis; Kokras, Nikolaos; Dalla, Christina; Antoniou, Katerina
Abstract: Cannabinoid administration during adolescence affects various physiological processes, such as motor and affective response, cognitive‐related functions and modulates neurotransmitter activity. Literature remains scant concerning the parallel examination of the effects of adolescent escalating low‐dose Δ 9 ‐tetrahydrocannabinol (Δ 9 ‐THC) on the behavioral and plasticity profile of adult rats in both sexes. Herein, we investigated the long‐term behavioral, neurochemical and neurobiological effects of adolescent escalating low Δ 9 ‐THC doses in adult male and female rats. In adult males, adolescent low‐dose Δ 9 ‐THC exposure led to increased spontaneous locomotor activity, impaired behavioral motor habituation and defective short‐term spatial memory, paralleled with decreased BDNF protein levels in the prefrontal cortex. In this brain area, serotonergic activity was increased, as depicted by the increased serotonin turnover rate, while the opposite effect was observed in the hippocampus, a region where SERT levels were enhanced by Δ 9 ‐THC, compared with vehicle. In adult females, adolescent Δ 9 ‐THC treatment led to decreased spontaneous vertical activity and impaired short‐term spatial memory, accompanied by increased BDNF protein levels in the prefrontal cortex. Present findings emphasize the key role of adolescent escalating low Δ 9 ‐THC exposure in the long‐term regulation of motor response, spatial‐related cognitive functions and neuroplasticity indices in adulthood. In this framework, these changes could, at a translational level, contribute to clinical issues suggesting the development of psychopathology in a sex‐differentiated manner following Δ 9 ‐THC exposure during adolescence. Abstract : Adolescent low‐dose Δ 9 ‐THC exposure increased spontaneous locomotion while impaired motor habituation and spatial memory in adult male rats. In the prefrontal cortex, decreased BDNF protein levels and increased serotonergic activity were observed, while in the hippocampus serotonergic activity was decreased and SERT levels were enhanced. In adult females, adolescent Δ 9 ‐THC exposure decreased spontaneous vertical activity, impaired spatial memory and increased BDNF levels in the prefrontal cortex.